2007
DOI: 10.1186/1471-2458-7-80
|View full text |Cite
|
Sign up to set email alerts
|

The association of self-esteem, depression and body satisfaction with obesity among Turkish adolescents

Abstract: BackgroundThe purpose of this study was to determine the prevalence of overweight and obesity and to examine the effects of actual weight status, perceived weight status and body satisfaction on self-esteem and depression in a high school population in Turkey.MethodsA cross-sectional survey of 2101 tenth-grade Turkish adolescents aged 15–18 was conducted. Body mass index (BMI) was calculated using weight and height measures. The overweight and obesity were based on the age- and gender-spesific BMI cut-off poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
1
21

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 39 publications
10
71
1
21
Order By: Relevance
“…This is consistent with previous studies that have found an association between these variables, such as that performed among Turkish adolescents by Ozmen in 2007 15 and by Almeida in Portugal in 2013. 9 This association might be mediated by bullying or chronic stress; the underlying mechanism is still unclear.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is consistent with previous studies that have found an association between these variables, such as that performed among Turkish adolescents by Ozmen in 2007 15 and by Almeida in Portugal in 2013. 9 This association might be mediated by bullying or chronic stress; the underlying mechanism is still unclear.…”
Section: Discussionsupporting
confidence: 82%
“…On the basis of data from previous studies, 15 a minimum sample size of 600 was established. Population 1 was the estimated proportion of people who had BID and depressive symptoms (30%) and population 2 was the estimated proportion of people without BID and depressive symptoms (20%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was found that most of the subjects were from low or middle socio-economical status. In a study, it was seen that being male and being from higher socio-economical level were predictors of overweight based on BMI (28). Similarly the prevalence of overweight and obesity was found to be higher in boys than in girls in Swedish (29), Canadian (30), Taiwanese (31) and Greek (32) adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of researches have shown that increased body weight is not associated with poor self-esteem and depression (Ozmen et al, 2007), but that thinness as a physical ideal, poor self-esteem and self-perception of their own bodies have significantly higher impact on dissatisfaction with appearance, then real increased physical weight (Canpolat et al, 2005). In a meta-analysis of the relationship between weight and self-esteem, Miller & Downey (1999) reported that even in children, perceived size was a better predictor of selfesteem than was actual body weight.…”
Section: The Frequency Of Results For the Variable "I Feel Good" (Osdo)mentioning
confidence: 99%